Aspectos clínico-patológicos do envenenamento botrópico experimental em equinos - SOUSA, Melina Garcia Saraiva de (2012)
The clinical and pathological alterations in horses, experimentally inoculated with Bothropoides jararaca, Bothrops jararacussu, Bothrops moojeni and Bothropoides neuwiedi poisons, were studied with the purpose to supply subsidies for the diagnosis of the poisoning. The liofilized poisons were diluted in 1ml of physiologic solution and subcutaneously administered to six horses, at doses of 0.5 and 1mg/kg (B. jararaca), 0.8 and 1.6mg/kg (B. jararacussu), 0.205mg/kg (B. moojeni) and 1mg/kg (B. neuwiedi). All horses, less those that received the poison of B. jararacussu, died The clinical signs began between 8min and 2h10min after the inoculation. The clinical course varied, in the four cases of lethal exit, from 24h41min to 70h41min, and was 16 days in the two horses that recovered,. The clinical picture, independent of the poison type and doses, was characterized by tumefaction at the site of inoculation, dragging on the ground with the hooves of the inoculated leg, inquietude, apathy, decrease of reaction to external stimuli, pale mucous membranes and hemorrhages. Laboratory exams revealed normocytic normochrômic anemia with progressive decrease in the number of erythrocytes, of hemoglobin and of the hematocrit, and leucocytosis due to neutrophilia. There was increase of alamina aminotransferase, creatinaquinase, lactic dehydrogenase, ureia and glucose, as well increase of the time of activation of protrombin and partial tromboplastina. At postmortem examination, the main findings were extensive hemorrhagic areas in the subcutaneous tissue, with the presence of non-coagulated blood, to a large degree associataed with edema (hemorragic edema), which extended from the inoculation site of the venom to the cervical, thoraxic and scapular region, and to the leg. In the periphery of the hemorragic areas existed gelatinous edema. There were great amounts of sanguinary liquid in the thoracic, pericardic and abdominal cavities. No significant histological alterations were found.